1997
DOI: 10.1093/tropej/43.2.84
|View full text |Cite
|
Sign up to set email alerts
|

A case control study of neonatal sepsis: experience from Saudi Arabia

Abstract: Sixty-one cases of neonatal septicaemia (NNS) identified by positive blood cultures during surveillance of infection at King Fahd Hospital of the University in Khobar, Saudi Arabia from September 1983-September 1988 were studied to evaluate the local pattern of pathogens and the risk factors for sepsis using a case control analysis. The incidence of NNS was 4.9 per 1000 live births (LB). Among inborn infants, birth weight specific sepsis rate ranged from 2 per 1000 liveborns among infants with birth weight > o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
47
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 0 publications
23
47
0
Order By: Relevance
“…Prematurity and low birth weight are usually associated with neonatal sepsis and mortality, which may be related to the fact that these neonates require prolonged hospitalization and interventions which predispose them to increased risk of hospital acquired infection or related to innate immunological deficiency. 8,9,10 In this study,59.16% were preterm deliveries. Dasoky HA et al 2 , Zakariya BP et al 11 Jain NK et al 12 also…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Prematurity and low birth weight are usually associated with neonatal sepsis and mortality, which may be related to the fact that these neonates require prolonged hospitalization and interventions which predispose them to increased risk of hospital acquired infection or related to innate immunological deficiency. 8,9,10 In this study,59.16% were preterm deliveries. Dasoky HA et al 2 , Zakariya BP et al 11 Jain NK et al 12 also…”
Section: Discussionmentioning
confidence: 47%
“…were statistically important risk factors of neonatal mortality in the present study ( Table -5), which was also reported by others. 8,9,10 Maternal fever was the most common maternal risk factor (67.5%) in our study. Hasan MS et al 13 also reported the finding of maternal fever (78.6% ) as an important independent factor in their studied subjects.…”
Section: Discussionmentioning
confidence: 48%
“…17 Birth weight is a well recognized risk factor for sepsis. 18,19,20,21,22 As gestational age is not always assessed accurately, and birth weight is taken as a better variable. Though association of low birth weight(LBW) with neonatal sepsis was significantly found in other studies , 13,14,17,21 , unfortunately our study showed insignificant result(P<0.841).…”
Section: Discussionmentioning
confidence: 99%
“…61%) or Pakistan (42% versus 58%), where LOS is more common. 29,32,33 The possible explanation for a lower frequency of LOS in this study might be the early discharge policy in the hospital.…”
Section: Discussionmentioning
confidence: 77%